2009
DOI: 10.1080/00103620802647116
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Quantification of Phytate in Animal Manure

Abstract: Phytate (inositol hexaphosphate) has been identified as a major organic phosphorus (P) form in soil, animal manure, and other environmental samples. Although a number of methods are available for quantitative isolation and determination of phytate, they are time-consuming and not amenable to routine analysis. We developed a simple, rapid method for enzymatic determination of phytate in animal manure. Animal manure was extracted by H 2 O, 1 M hydrochloric acid (HCl), 0.1 M sodium acetate (NaOAc, pH 5.0) with or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…2). These results agree with the literature (He and Honeycutt, 2001; He et al, 2004a, 2007, 2009, 2010).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…2). These results agree with the literature (He and Honeycutt, 2001; He et al, 2004a, 2007, 2009, 2010).…”
Section: Resultssupporting
confidence: 93%
“…Turner and Leytem (2004) reported that the P recovery from the sequential fractionation was 94, 79, and 92% for broiler litter, cattle manure, and swine manure, respectively, values that are similar to those reported in this study (98, 77, and 92% for chicken, dairy, and swine manures, respectively) ( Table 2). He et al (2009) also reported incomplete recovery of P t during the fractionation scheme.…”
Section: Relationships Between Total Dry Ash Phosphorus Fractionatedmentioning
confidence: 96%
“…These two P pools were selected primarily for their predominance and impact on coproduct P bioavailability. Due to procedural simplicity and its widespread use for soil and manure extracts (Toor et al, 2003; He et al, 2009), we used the enzymatic hydrolysis method to quantify the phytate‐P fraction.…”
Section: Recommendations For Phosphorus Content In the Diet For Variomentioning
confidence: 99%
“…Inorganic P (also known as phosphate P or free P) has higher bioavailability than phytate P. The rest of P represents the sum of all P-containing compounds in a sample other than phytate P and inorganic P. It includes, for example, P found in DNA, RNA, proteins, phospholipids and starch. Since phytate P is not well utilized by monogastric animals, it contributes to increased P discharge into the environment (He et al, 2009). In addition, phytate has been shown to interact directly and indirectly with various dietary components, and in particular certain minerals such as Ca and Zn, and thus reduces their availability to humans and animals (Bohn et al, 2008).…”
Section: Introductionmentioning
confidence: 99%